Pengaruh Pola Asuh Demokratis Terhadap Kematangan Emosional Remaja Akhir - Anas, Desti Ramadhani; Daud, Muh; Ansar, Wilda (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Adolescence is a period of development from childhood to adulthood, which involves increasingly mature emotional development, especially when given appropriate parenting.The purpose of this research is to determine the effect of democratic parenting on the emotional maturity of late adolescents. Respondents in this study were 245 people with a dominant to very dominant democratic parenting pattern. The significance based on exponential regression analysis is 0.000, meaning that there is an influence between democratic parenting and emotional maturity. Based on the R Square value or the coefficient of determination, a value of 0,403 is obtained. Therefore, democratic parentinghas a contribution of 40.3% on the emotional maturity of late adolescents, and the other 59.7% is influenced by other factors outside of democratic parenting. The results of data analysis using exponential regression analysis which shows an R value of 0.635. Thus it can be seen that democratic parenting and emotional maturity have a strong correlation coefficient. The implication of this research is that it can make a contribution to the scienceof developmental psychology, especially in the emotional development of adolescents and the provision of proper and appropriate parenting to children.